Mitophagy: A Potential Target for Pressure Overload-Induced Cardiac Remodelling. (27th September 2022) - Shao, Ruochen; Li, Junli; Qu, Tianyi; Liao, Yanbiao; Chen, Mao
Abstract : The pathological mechanisms underlying cardiac remodelling and cardiac dysfunction caused by pressure overload are poorly understood. Mitochondrial damage and functional dysfunction, including mitochondrial bioenergetic disorder, oxidative stress, and mtDNA damage, contribute to heart injury caused by pressure overload. Mitophagy, an important regulator of mitochondrial homeostasis and function, is triggered by mitochondrial damage and participates in the pathological process of cardiovascular diseases. Recent studies indicate that mitophagy plays a critical role in the pressure overload model, but evidence on the causal relationship between mitophagy abnormality and pressure overload-induced heart injury is inconclusive. This review summarises the mechanism, role, and regulation of mitophagy in the pressure overload model. It also pays special attention to active compounds that may regulate mitophagy in pressure overload, which provide clues for possible clinical applications.